Medidor de emissão de CO2 e CH4 em reservatório de usinas hidrelétricas nas superfícies aquáticas: contribuição para a extensão de modelo robótico - Miskalo, Bianca Borsato (2020)
The recent intensification of human activities has led to a significant increase in the emission of certain gases, called greenhouse gases (GHG), such as carbon dioxide (CO2) and methane (CH4). The Earth's climate changes caused by the excess of these gases have caused world communities to come together through United Nations (UN) Organizations to create strategies to reduce the impacts of gases in the Earth's atmosphere. Of all the GHG generating activities, the energy sector is the one that most contributes to global warming, the reservoirs of hydroelectric plants are potential emitters of greenhouse gases. Considering the importance of developing new policies to slow global warming, the proposed work makes use of a study performed for an automated gas emission measurement tool, which allows to identify an estimated amount of pollution in reservoirs that a hydroelectric plant is capable of producing and emitting to the atmosphere. Currently, this measurement is performed using stationary sensors manually positioned with the aid of boats. The robotic model allows data collection through gas sensors and moves around the water surface by means of engines and guided by GPS. The prototype was applied to a reservoir at the Mourão Hydroelectric Plant in the city of Campo Mourão in Paraná. The prototype obtained a good performance during the tests on aquatic surfaces, considering that the reservoir under study is deactivated, being used only for leisure, the data presented a low level of greenhouse gas emissions at the site. The data collected contribute to the studies for the elaboration of methods for recovering water conditions, regardless of the location applied, through preservation actions.